THE INFLUENCE OF SYSTEM QUALITY, EDUCATOR, MOTIVATION ON SATISFACTION AND INTENTION TO CONTINUE ON CLASS X STUDENTS WHO USE E-LEARNING AT SMAK St. LOUIS 1 SURABAYA - Regina Anthonia Fernandez, Ester; Lengga Tiala, Agustinus (PT. BATARI EDU CALYA, 2023)
Advances in technology and communication are expected to provide effective and efficient performance for educators in the current millennial era, especially in the conditions of a pandemic due to the COVID-19 outbreak that has infected the world, including Indonesia, especially in the city of Surabaya. The purpose of this study is to examine and analyze changes in the quality of the education system, and the challenges for educators in operating e-learning applications to deliver learning materials, to attract student interest in learning and bold interactions. Motivation becomes the driving force in students. They will judge the perceived usefulness by achieving satisfaction or not. Because it affects their intention to continue using the bold system, by still choosing the high school they chose switching to homeschooling or choosing not to continue school. The research method used consists of research design, variables, operational definitions, and data sources, research instruments, the population is class X students at SMAK St. Louis 1 Surabaya, samples taken were 334 respondents from class X students who were asked questions. The procedure for distributing questionnaire data through Google Forms, as well as data analysis techniques using SEM using Lisrel software. The reliability test shows (6) the reliability variable. This study obtained the results of hypothesis testing that had a positive and significant effect on the system quality, educator, and motivation variables on satisfaction, then the satisfaction variable on the intention to continue. Satisfaction mediates the relationship between system quality and the intention to continue has a positive and significant effect, while the satisfaction hypothesis mediates the relationship between motivation and intention to continue and has a positive and insignificant effect